Unpacking the notion of ‘criticality’ in liberatory praxis: A critical pedagogy perspective - Nomdo, Gideon (Critical Studies in Teaching and Learning, 2023)
This paper is informed by the field of socially just pedagogies. A critical pedagogy perspective grounded in a transformative and liberatory praxis is employed to discuss why the notion of criticalityis fundamental to classroom engagement, especially within historically white South African universities. Although widely adopted, the meanings attached to criticality varies. This paper focusses on criticality as used within critical pedagogy and argues that it ushers in a humanising classroom pedagogy that facilitates dialogic relationships and promotes student agency and critical social consciousness. Through employing a qualitative case study methodology, this research draws on data extracted from two courses on identity. Acritically reflective gaze is adopted to examine the impact of criticality in these spaces. Criticality embedded in dialogic praxis was found to aid the development of agency and raise critical awareness about socially just societies. Teachers’ responsibilities for being agents of change, was also highlighted.